Leveraging Interdisciplinary Teams to Develop and Implement Secure Websites for Behavioral Research: Applied Tutorial - Martin, Christie L; Kramer-Kostecka, Eydie N; Linde, Jennifer A; Friend, Sarah; Zuroski, Vanessa R; Fulkerson, Jayne A (JMIR Publications, 2020)
Behavioral researchers are increasingly using interactive digital platforms, either as standalone or supplementary intervention tools, to facilitate positive changes in research participants' health habits. Research-oriented interactive websites optimally offer a variety of participatory mediums, such as blogs, user-driven content, or health activities. Owing to the multidirectional features of interactive websites, and a corresponding need to protect research participants' identity and data, it is paramount that researchers design ethical platforms that ensure privacy and minimize loss of anonymity and confidentiality. Authentication (ie, digital verification of one's identity) of interactive sites is one viable solution to these concerns. Although previous publications have addressed ethical requirements related to authenticated platforms, few applied guidelines in the literature facilitate adherence to ethical principles and legally compliant study protocols during all phases of research website creation (feasibility, design, implementation, and maintenance). Notably, to remain compliant with ethical standards and study protocols, behavioral researchers must collaborate with interdisciplinary teams to ensure that the authenticated site remains secure and usable in all stages of the project. In this tutorial, we present a case study conducted at a large research university. Through iterative and practical recommendations, we detail lessons learned from collaborations with the Institutional Review Board, legal experts, and information technology teams. Although the intricacies of our applied tutorial may require adaptations based on each institution's technological capacity, we are confident that the core takeaways are universal and thus useful to behavioral researchers creating ethically responsible and compliant interactive websites.